Electrocatalytic oxidation of readily available disaccharides in alkaline medium at gold electrode - Parpot, Pier (2010)
The electrooxidation of some readily available disaccharides, i.e. trehalose, maltose, isomaltulose and cellobiose, was investigated in alkaline medium. The reaction products were identified and quantified using chromatographic and spectroscopic methods. Important conversion yields and high selectivities towardsmonocarboxylic acids of some of these disaccharides were obtained. ThepHeffect on the product distribution was also determined.